Increased availability of NADH in metabolically engineered baker's yeast improves transaminase-oxidoreductase coupled asymmetric whole-cell bioconversion. Issue 1 (December 2016) - Knudsen, Jan; Hägglöf, Cecilia; Weber, Nora; Carlquist, Magnus
Abstract Background Saccharomyces cerevisiae can be engineered to perform a multitude of different chemical reactions that are not programmed in its original genetic code. It has a large potential to function as whole-cell biocatalyst for one-pot multistep synthesis of various organic molecules, and it may thus serve as a powerful alternative or complement to traditional organic synthetic routes for new chemical entities (NCEs). However, although the selectivity in many cases is high, the catalytic activity is often low which results in low space-time-yields. In the case for NADH-dependent heterologous reductive reactions, a possible constraint is the availability of cytosolic NADH, which may be limited due to competition with native oxidative enzymes that act to maintain redox homeostasis. In this study, the effect of increasing the availability of cytosolic NADH on the catalytic activity of engineered yeast for transamination-reduction coupled asymmetric one-pot conversion was investigated. Results A series of active whole-cell biocatalysts were constructed by over-expressing the (S )-selective ω-transaminase (VAMT ) fromCapsicum chinense together with the NADH-dependent (S )-selective alcohol dehydrogenase (SADH ) originating fromRhodococcus erythropolis in strains with or without deletion of glycerol-3-phosphate dehydrogenases 1 and 2 (GPD1 andGPD2 ). The yeast strains were evaluated as catalysts for simultaneous: (a) kinetic resolution of theracemic mixture to (R )-1-phenylethylamine, and (b) reduction of the produced acetophenone to (S )-1-phenylethanol. For thegpd1 Δgpd2 Δ strain, cell metabolism was effectively used for the supply of both amine acceptors and the co-factor pyridoxal-5′-phosphate (PLP) for the ω-transaminase, as well as for regenerating NADH for the reduction. In contrast, there was nearly no formation of (S )-1-phenylethanol when using the control strain with intactGPD s and over-expressing theVAMT -SADH coupling. It was found that agpd1 Δgpd2 Δ strain over-expressingSADH had a 3-fold higher reduction rate and a 3-fold lower glucose requirement than the strain with intactGPD s over-expressingSADH . Conclusions Overall the results demonstrate that the deletion of theGPD1 andGPD2 genes significantly increases activity of the whole-cell biocatalyst, and at the same time reduces the co-substrate demand in a process configuration where only yeast and sugar is added to drive the reactions, i.e. without addition of external co-factors or prosthetic groups.